Consumer Protection on the Trade of Stolen Goods at Marketplace in the Perspective of Maslahah Mursalah (Case Study at Facebook Marketplace) - Syafiq, Muhammad; Hasanah, Uswatun (AL-IKTISAB: Journal of Islamic Economic Law, 2024)
Trading stolen goods on online platforms, such as Facebook marketplace, is a serious consumer protection issue. This research aims to determine the implementation of forms of trading in stolen goods on the Facebook marketplace, forms of legal protection for consumers, as well as consumer protection against trading in stolen goods from the perspective of maslahah mursalah. This research uses empirical (juridical analysis) and qualitative research methods, where this research uses empirical facts and laws. The research results show that trading in stolen goods on Facebook marketplace includes various types of goods with legal risks for perpetrators and consumers. Existing legal protection, based on the Information and Electronic Transactions Law (ITE Law) and the Criminal Code (KUHP), provides the basis for taking action against perpetrators of trafficking in stolen goods and protecting consumer rights. From maslahah mursalah perspective, consumer protection emphasizes justice and public benefit, as well as avoiding detrimental transactions. This research emphasizes the importance of legal and ethical awareness in online transactions to prevent and deal with trafficking in stolen goods.